Exploring the mechanical behavior of friction material composites using artificial intelligence - Matté, Daniel (My University, 2025)
The application of artificial intelligence techniques is becoming increasingly valuable for several areas of knowledge, allowing extracting information, predict patterns, work with complex problems, and generate solutions that would not be achievable by other techniques without an extremely high computational cost or else numerous physical experiments, with high execution costs and which often do not achieve the desired result. In this work, artificial intelligence (AI) was used to create mathematical models for four properties of friction material composites from an extensive database containing the chemical composition and the respective mechanical properties. An algorithm capable of predicting mechanical results of friction materials based on chemical composition, optimizing an existing composition, and proposing new (previously nonexistent) compositions was proposed based on the desired values of each mechanical property. The algorithm combines rule-based instructions, neural networks, and particle swarm optimization. Physical samples based on the algorithm prediction were produced, making it possible to assess the predictive power of the models and better understand the improvements needed for predicting new friction materials. Notably, artificial neural networks, once trained, demonstrated an average root mean square error (RMSE) that was 30.8 % smaller compared to using multilinear fittings to predict new results from previously non-existent compositions. [resumo fornecido pelo autor]
A aplicação de técnicas de inteligência artificial está se tornando cada vez mais valiosa para diversas áreas do conhecimento, pois permite extrair informações, prever padrões, trabalhar com problemas complexos e gerar soluções que não seriam alcançáveis por outras técnicas sem um custo computacional extremamente elevado ou então, inúmeras experimentos físicos, com altos custos de execução e que muitas vezes não alcançam o resultado desejado. Neste trabalho, a inteligência artificial (IA) foi utilizada para criar modelos matemáticos para quatro propriedades de compósitos de materiais de atrito a partir de um extenso banco de dados que contém a composição química e suas propriedades mecânicas. Foi proposto um algoritmo capaz de prever resultados mecânicos de materiais de atrito com base na composição química, otimizar uma composição existente e propor novas composições (até então inexistentes) com base nos valores desejados de cada propriedade mecânica. O algoritmo combina instruções baseadas em regras, redes neurais e otimização de enxame de partículas. Foram produzidas amostras físicas baseadas na previsão do algoritmo, que possibilitaram avaliar o poder preditivo dos modelos e entender melhor a necessidade de melhorias na ferramenta construída para previsão de novos materiais de atrito. Notavelmente, as redes neurais artificiais, uma vez treinadas, demonstraram um erro quadrático médio médio (RMSE) que foi 30,8 % menor em comparação com o uso de ajustes multilineares para prever novos resultados de composições anteriormente inexistentes. [resumo fornecido pelo autor]
Keywords: Materiais de atrito; Aprendizado do computador; Inteligência artificial; Friction materials; Machine learning; Artificial intelligence